Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Gao, Yajuan; Han, Hongbin; Du, Jichen; He, Qingyuan; Jia, Yanxing; Yan, Junhao; Dai, Hui; Cui, Bin; Yang, Jing; Wei, Xunbin; Yang, Liu; Wang, Rui; et al. (Science China. Life sciences, 2022)
The smooth transportation of substances through the brain extracellular space (ECS) is crucial to maintaining brain function; however, the way this occurs under simulated microgravity remains unclear. In this study, tracer-based magnetic resonance imaging (MRI) and D ECS -mapping techniques were used to image the drainage of brain interstitial fluid (ISF) from the ECS of the hippocampus in a tail-suspended hindlimb-unloading rat model at day 3 (HU-3) and 7 (HU-7). The results indicated that drainage of the ISF was accelerated in the HU-3 group but slowed markedly in the HU-7 group. The tortuosity of the ECS decreased in the HU-3 group but increased in the HU-7 group, while the volume fraction of the ECS increased in both groups. The diffusion rate within the ECS increased in the HU-3 group and decreased in the HU-7 group. The alterations to ISF drainage and diffusion in the ECS were recoverable in the HU-3 group, but neither parameter was restored in the HU-7 group. Our findings suggest that early changes to the hippocampal ECS and ISF drainage under simulated microgravity can be detected by tracer-based MRI, providing a new perspective for studying microgravity-induced nano-scale structure abnormities and developing neuroprotective approaches involving the brain ECS.